2022
DOI: 10.1101/2022.01.12.476053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antisense oligonucleotides targeting the miR-29b binding site in the GRN mRNA increase progranulin translation

Abstract: Loss-of-function GRN mutations result in progranulin haploinsufficiency and are a common cause of frontotemporal dementia (FTD). Antisense oligonucleotides (ASOs) are emerging as a promising therapeutic modality for neurological diseases, but ASO-based strategies for increasing target protein levels are still relatively limited. Here, we report the use of ASOs to increase progranulin protein levels by targeting the miR-29b binding site in the 3′ UTR of the GRN mRNA, resulting in increased translation.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…For example, an 18-mer ASO targeting an intronic splicing silencer increased the inclusion of exon 7 of SMN2 in a humanized mouse model of spinal muscular atrophy [32]. Additionally, we recently showed that an 18-mer ASO that blocks a miR binding site in the GRN mRNA increases progranulin protein levels in a humanized mouse model [33]. Nonetheless, future studies could test ASOs of different lengths, such as 20-mers, targeting this same EJC region of the Grn R493X mRNA.…”
Section: Plos Onementioning
confidence: 97%
See 1 more Smart Citation
“…For example, an 18-mer ASO targeting an intronic splicing silencer increased the inclusion of exon 7 of SMN2 in a humanized mouse model of spinal muscular atrophy [32]. Additionally, we recently showed that an 18-mer ASO that blocks a miR binding site in the GRN mRNA increases progranulin protein levels in a humanized mouse model [33]. Nonetheless, future studies could test ASOs of different lengths, such as 20-mers, targeting this same EJC region of the Grn R493X mRNA.…”
Section: Plos Onementioning
confidence: 97%
“…These results further suggest that alternative strategies should be pursued for increasing progranulin levels in the context of progranulin-deficient FTD. One such potential strategy is to use ASOs to block miR binding sites, such as miR-659 and miR-29b [35][36][37][38], in the 3' UTR of the GRN mRNA [33]. A notable advantage of this miR-targeting strategy is that it is agnostic to the specific disease mutation and could be used in the context of any of the >70 FTD-associated GRN mutations that have been identified [15].…”
Section: Plos Onementioning
confidence: 99%
“…Steric blocking ASOs can also target regulatory sequences and structures in the untranslated regions (UTRs). This interaction can stabilize transcripts and increase target protein levels [75,76]. Finally, steric blocking ASOs can also be employed to prevent the translation of a transcript by the ribosomes, reducing protein levels [77,78].…”
Section: Aso Treatment Modalitiesmentioning
confidence: 99%
“…This can be achieved through different mechanisms, such as skipping exons (including cryptic exons) and exon inclusion. ASOs are also able to influence protein levels by targeting the untranslated regions (UTRs) [16,17]. Here, the ASOs are not modifying splicing, but by sterically blocking regulatory elements, they can influence the stability of a transcript.…”
Section: Splice-switching Asosmentioning
confidence: 99%